PENYELESAIAN TINDAK PIDANA PENGRUSAKAN ALAT PERAGA KAMPANYE DALAM PEMILIHAN KEPALA DAERAH KOTA DUMAI TAHUN 2015 BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 2015 TENTANG PEMILIHAN GUBERNUR BUPATI DAN WALIKOTA - Agung Prayogi; Erdianto '; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The local elections is a form of political participation of the people in a democracy, the cleanliness , honesty and fairness implementation of the local elections will reflect the quality of democracy in the countries concerned . In order to preserve the purity of prospective head region that is essential for democracy .The problem in this thesis is the completion of the crime of destruction of props during the provincial election campaign Dumai city in 2015 by Law No. 8 of 2015 on the election of governors, regents and mayors? Barriers to what was found by law enforcement agencies in solving the crime of destruction of props during the provincial election campaign Dumai city in 2015 by Law No. 8 of 2015 on the election of governors, regents and mayors? as for the purpose of this study was to determine how to resolve the crime of destruction of props campaign in local elections Dumai 2015 by Law No. 8 of 2015 on the election of governors, regents and mayors, to know what barriers found by law enforcement officers in completing the crime of destruction of props during the provincial election campaign Dumai city in 2015 by Law No. 8 of 2015 on the election of governors, regents and mayors.This type of research can be classified as socio-juridical , because in this study the authors directly conduct research on the locations or places studied in order to give a complete and clear picture of the problems studied . The research location KPU Kota Dumai and Dumai City Police Resort . This data collection techniques with interviews and a literature review .Based on the results of research show that in the completion of the crime of destruction of props during the provincial election campaign Dumai 2015 , did not run in accordance with the applicable rules because there are no obstacles in its implementation . Barriers is: their limitations very short time that is later than 7 days after the destruction of props campaign , and limited personnel owned by Panwaslu , the ability to conduct an investigation at all that is not owned by a member of the Election Supervisory Committee , as well as the Commission does not have the authority to do search and seizure .Keywords : Settlement - Crime - Campaign Viewer Tool - Regional Head